Lignin monomeric composition of corks from the barks of Betula pendula, Quercus suber and Quercus cerris determined by Py–GC–MS/FID - Marques, António Velez; Pereira, Helena (Journal of Analytical and Applied Pyrolysis, 2012)
Samples of cork tissues separated from the barks of Betula pendula, Quercus suber and Quercus cerris were characterized by Py–GC–MS/FID in respect to composition of lignin. The pyrolysis temperature influenced the yield of pyrolysis products, and in the conditions usually applied to wood pyrolysis (550 ◦C) suberin is only partially degraded into products. The lignin composition of the three corks showed predominantly a guaiacyl-based lignin: guaiacyl (G) units represented 85.7%, 96.4% and 93.7% of lignin respectively in B. pendula, Q. suber and Q. cerris corks, while syringyl (S) units amounted respectively to 11.9%, 2.5% and 2.7% and p-hydroxyphenyl (H) units to 2.4%, 1.1% and 3.6%. Pyrolysis of the woods of these same species confirmed the GS character of their lignins in contrast to the corks G-lignin type. The influence of ferulic acid in the results and its integration in a heterogeneous cork lignin structure was discussed.
Keywords: Betula pendula; Cork; Lignin composition; pyrolysis; Quercus cerris; Quercus suber

Study of thermochemical treatments of cork in the 150–400°C range using colour analysis and FTIR spectroscopy - Şen, Ali; Marques, António Velez; Gominho, Jorge; Pereira, Helena (Industrial Crops and Products, 2012)
A study of chemical transformations of cork during heat treatments was made using colour variation and FTIR analysis. The cork enriched fractions from Quercus cerris bark were subjected to isothermal heating in the temperature range 150–400 ◦ C and treatment time from 5 to 90min. Mass loss ranged from 3% (90min at 150 ◦ C) to 71% (60min at 350 ◦ C). FTIR showed that hemicelluloses were thermally degraded ﬁrst while suberin remained as the most heat resistant component. The change of CIE-Lab parameters was rapid for low intensity treatments where no signiﬁcant mass loss occurred (at 150 ◦ C L* decreased from the initial 51.5 to 37.3 after 20min). The decrease in all colour parameters continued with temperature until they remained substantially constant with over 40% mass loss. Modelling of the thermally induced mass loss could be made using colour analysis. This is applicable to monitoring the production of heat expanded insulation agglomerates.
Keywords: Colour analysis; Cork; FTIR; Heat treatment; Quercus cerris